Nature and Culture in Humanistic Studies. - Gill, Russell (International Journal of the Humanities, 2005)
It is increasingly common to find attempts to open up the circularity of humanistic studies by appeals to the outside, scientific methodologies of cognitive studies and biology. Embracing the goals of ‘embodied criticism,’ we are more likely to escape the recycling of ideas that occurs when humanistic studies are regarded as closed systems and criticism becomes an examination of differences with the system. But we can also understand why the re-examination of closed systems remains aesthetically pleasing. The theme-and-variation nature of this recycling appeals to our innate love of patterns. The reduction of complexity is a more immediate route to action than is consideration of complexities like broken myths. The bindings within the brain of multiple inputs into unified perceptions and the hypostatizations of language encourage simplified thinking. Although dangers are written all over considerations like these, the pleasures and usefulness of the artifacts of culture are inescapable. We would do well to develop a disposition that can accommodate these differences rather than strive to reconcile them. Emotionally, we may yearn for unity, but it is pluralism that we must learn to live with.